Metacognitive pattern in solving science problems: a study on an excellent student - Tan, Hui Li (2013)
This qualitative research examined an excellent student’s metacognitive thinking and strategies in solving science problems. A case study design was employed, one which involved the use of interview and observation to obtain information about metacognitive pattern in solving science problems. Research participant of this study was an excellent student (age of 11 years old) from a private primary school in Johor Bahru. The data generated from the observation on and the interview with the research participant were analyzed using three stages of coding (open coding, axial coding, and selective coding) to develop themes that explained the research participant’s metacognitive pattern in solving science problems. The derived themes were confirmed by two assessors, comprised of an English teacher and an academic with the expertise in educational psychology. The findings show that the excellent student involved particular metacognitive elements during each different phases of solving science problems. There is the interplay among metacognitive awareness and metacognitive regulation in certain phases. Furthermore, the findings also reveals that teacher gives much influence on the development of the student’s metacognitive pattern in solving science problems. Based on the findings, it implies that developing children’s metacognition must be emphasized in school to improve their ability to solve problems. The present study suggests that teachers need to design and implement teaching and learning approaches or strategies that can enhance students’ metacognitive abilities. This facilitates the success of developing children into higher-order thinkers in order to meet the expectation of Kurikulum Standard Sekolah Rendah (KSSR) in primary school as inspired by Malaysia Education Blueprint 2013- 2025.